2012
DOI: 10.1080/13597566.2012.688269
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: Policy-making, Learning and Devolution

Abstract: This collection explores the idea that devolution in European states can provide 'laboratories of democracy' as states experiment in different ways to address social and economic problems and engage their citizens. While there is a substantial literature on policy diffusion and learning among US states, and on transfer and learning between countries, there is not much on learning among European federated and devolved governments. This collection fills that gap with a series of studies based primarily on experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…In addition, there was a contribution from the United States (US), notably Senator George Mitchell's chairing of the talks. But, as shown below, other actors in the wider policy community, discussed by Keating and Cairney (2012) and Dolowitz and Marsh (1996), played key roles in clothing the policy bones of the constitutional skeleton.…”
Section: Directions and Channels For Learning: The Policies Involvedmentioning
confidence: 97%
See 3 more Smart Citations
“…In addition, there was a contribution from the United States (US), notably Senator George Mitchell's chairing of the talks. But, as shown below, other actors in the wider policy community, discussed by Keating and Cairney (2012) and Dolowitz and Marsh (1996), played key roles in clothing the policy bones of the constitutional skeleton.…”
Section: Directions and Channels For Learning: The Policies Involvedmentioning
confidence: 97%
“…In conclusion, it is suggested that it is not only because of the banking, fiscal and economic crises in Ireland and the UK that learning opportunities have been undermined. This case study demonstrates the importance of the contrast between politicians with their "limited attention spans" (Keating and Cairney, 2012) and the more analytical wider policy community of professionals and interest groups. Power relations between them are a significant factor in degrees of superficiality or profundity.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In practice, the devolved UK has an asymmetrical constitution in that the new territorial institutions were granted substantially different powers and responsibilities (Keating and Cairney ). This resulted in re‐balancing central and regional autonomies, as demonstrated by the delineation of reserved powers (Westminster) and variegated devolved powers to the nation‐regions of Scotland, Wales and Northern Ireland.…”
Section: Introductionmentioning
confidence: 99%